(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
This researchwas conducted for the first time in Syria in order to studytheeffect of eyestalk ablation on moulting and ovarian maturation in PenaeusSemisulcatusas on essential step in most shrimp hatcheries . 12 females 15,5-17,5 cm and 6 adult males with a length of 14-16 cm were colectedat the sublittoal zone of city Jableh during the period from the beginning of the month of April 2012 until the end of June 2013. Eyestalks for 6 females were ablated while other females were left as control, and females were gathered with males by 2 : 1 in 150 L- tank connected to the basin ’s filtering, controlled temperature range between 27-29 co and 38 ‰ salinity and oxygen dissolved 4 mg / l , Animals were fed individual once daily at a rate of 12 % of body weight with stuffed squid and shrimp. the study showed that all femaleswith eyestalk ablation were molted during the period of 2-6 days, the ovaries of five females began activeand one of female died, while females withnon of eyestalk ablation over a period of 8-20 days and ovaries oftwoof them showed development. تناول هذا البحث لأول مرة في سورية تأثير استئصال السويقة العينية في الانسلاخ، ونضوج المبايض عندالنوع PenaeusSemisulcatusالتي أصبحت خطوة أساسية في معظم مفارخ الجمبري. تم انتقاء 12أنثى بطول15,5-17,5 سم، و6 ذكور بالغة بطول تراوح بين14-16 سم، وذلك من المنطقة تحت الشاطئية لمدينة جبلة خلال الفترة الممتدة من بداية شهر نيسان2012 وحتى نهاية شهر حزيران 2013. استئصلت السويقة العينية لـ 6إناث, بينما بقيت الإناثالأخرى بوصفها شاهده.وضعت الإناث مع الذكور بنسبة 2:1 في كل حوض سعة150 ل موصولة إلى حوض فلتره, حيثضبطت درجة الحرارة على 27-29 م0،وملوحة 38 ‰،وأوكسجين منحل لايقل عن4 مغ/ ل, تم تغذية الأفراد مرة واحدة يومياً بمعدل 12% من وزن الجسم بلحم الحبار والجمبري. بينت الدراسة أنكلالإناثمستأصلة السويقة انسلخت خلال فترة 6-2 أيام، وبدأت مبايض5منها بالتطور في حين نفقت أنثى واحدة فقط, بينما حدث الانسلاخ عند الإناث غير مستأصلة السويقة العينية خلال فترة من 8ـ 20 يوماً، وتطورت مبايض اثنين منها فقط.